Predictive factors of hospital stay in patients with odontogenic maxillofacial infections: the role of C-reactive protein. Issue 4 (May 2017) - Stathopoulos, P.; Igoumenakis, D.; Shuttleworth, J.; Smith, W.; Ameerally, P.
Abstract: To investigate whether clinical or laboratory variables on admission of patients with odontogenic infections are associated with a severe clinical course and a prolonged hospital stay, we hypothesised that specific factors such as the serum concentration of C-reactive protein (CRP) may act as predictors of the duration of stay. We designed a prospective patient-oriented study that included all those treated for maxillofacial infections of odontogenic origin in the Oral and Maxillofacial Surgery Department of Northampton General Hospital between November 2013 and December 2014. A total of 71 were enrolled. We found that the concentration of CRP was a significant predictor of hospital stay (p = 0.01). Its measurement on admission can predict the likely duration of stay of these patients and enable beds to be managed more efficiently.